PEMBERDAYAAN KOPERASI MELALUI SOSIALISASI DAN PEMBUATAN WEBSITE LAPORAN KEUANGAN DI KELURAHAN KETABANG - Bahri, Dien Fairuz Dzakiyyah; Arujie, Izza Rasuna; Izzah, Nurul; Irsyadhie, Muhammad Rafi; Nabila, Nadhea Khoirun; Sumiarsa, Fitri Fadhilah (ABIDUMASY, 2026)
Koperasi Simpan Pinjam (KSP) plays a strategic role in strengthening the people's economy, but still faces various challenges, particularly in financial reporting and the use of information technology. This community service aims to improve the financial and digital literacy of the board members of Koperasi Merah Putih in Ketabang Sub-district, Surabaya, through two integrated approaches: socialization of cooperative financial reporting and the development of a website-based information system. The activity was carried out participatively by involving cooperative board members in every stage, from observation, socialization, website development, to training on system usage. The website was developed using PHP programming language and includes key features such as transaction recording, member management, and financial reporting. The results of the activity showed an increase in the board members' understanding of financial reporting and initial adoption of digital technology, although challenges remain in adapting to technology due to limited human resources. This activity demonstrates that the integration of financial literacy and digitalization of cooperative information systems can strengthen cooperative governance in a more accountable, efficient, and modern manner.